Twelve Years Later or Some Thoughts on International Conference Embeddedness and Beyond: Do Sociological Theories Meet Economic Realities?, Moscow, October 25–28, 2012 - Radaev, Vadim (Journal of Economic Sociology, 2013)
Detailed description in the text